EXPLORING ENHANCEMENTS TO THE AGILE APPROACH FOR MID-SIZED ENTERPRISES IN THE SERVICES SECTOR - Fourie, Lyndall; De Vries, Marne (The South African Journal of Industrial Engineering, 2017)
Companies need to thrive in a dynamic environment, responding to it in an agile way. Within a company’s ICT domain, a key to achieving agility is to use agile software development. Experience, together with a literature review, has shown that the agile software development family of methods does not naturally fit into the context of medium to large enterprises. This article focuses on the challenges associated with agile software development. The main contribution of the article is to affirm that a class-of-problems exists – i.e., that many practitioners face challenges in implementing existing agile software development approaches successfully in medium to large enterprises. We also gather data via multiple interviews to show that the class-of-problems exists in a real-world enterprise that currently applies agile software development in medium-sized governmental bodies.